Penggunaan Material Galian Dari Desa Kandang Mbelang, Lawe Bulan Untuk Pembuatan Aspal Beton Campuran Panas - Kasaf, Michel (Lembaga Riset Ilmiah, 2022)
Aggregate is the main component of the road pavement structure, which is 90-95% of the weight of the pavement. Such a large proportion causes the quality of the aggregate used will greatly determine the overall pavement performance. The availability of quality aggregates is necessary to ensure the sustainability of development in the road construction sector. One area that has aggregate potential that has not been optimally utilized is Kandang Mbelang Village, Lawe Bulan. The purpose of this study was to determine the characteristics of the Marshall, UCS, and ITS test values ​​and the permeability of the asphalt mixture using the excavated material of Kandang Mbelang, Lawe Bulan as an aggregate. This study used an experimental method carried out in the laboratory with variations in asphalt content of 4.5%, 5%, 5.5%, and 6% for Marshall testing and to obtain Optimum Asphalt Content (KAO). For testing ITS, UCS and permeability used Optimum Asphalt Content with three samples each. Hypothesis testing for data comparison using the T-test method. The use of Mbelang cage aggregate in the AC-WC spec IV mixture resulted in a stability value of 711.5 kg, a flow value of 3.48 mm, a porosity value of 16.077%, a density value of 2.016 gr/cm3 and Marshall Quotient value is 215.823 kg/mm ​​at Optimum Asphalt Content of 5.3%. The average ITS value is 319.024 KPa, the average UCS value is 6.982.237 KPa, and the average permeability coefficient is 7.14x10-4 cm/sec. Through the statistical method of T T-tests, it was found that the use of Mbelang cage aggregate for the AC-WC spec IV mixture did not change the stability, flow, I,TS, and UCS values.